Performance based automated control system design - Tan, Thiam Huat. (2008)
The objective is to employ the Genetic Algorithm to solve pole placement problem in context of H(infinity) control, using the framework of chain-scattering approach. The use of GA formulation is investigated to search for a bounded real free parameter S(s) such that the constraints for pole placement requirement are satisfied.